Chromogenic Black Stain pada Gigi Anak : Tinjauan Literatur - Septriyani Kaswindiarti; Khoirun Amala (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Stains are pigmented deposits on the surface of teeth, commonly caused by activities that increase the risk of discoloration, such as consuming colored beverages (e.g., coffee, tea, and soft drinks) and smoking, which leaves brownish to blackish tar residue. This discoloration typically develops gradually over time and can lead to aesthetic concerns. Such changes may have a significant psychological impact, particularly when they affect the anterior teeth, which are visible during speaking or smiling.Tooth discoloration can occur in both permanent and primary (deciduous) teeth. This condition is especially important to address in children, as teeth play a vital role in their growth and development. In childhood, teeth function not only as tools for chewing but also assist in speech development, facial balance, and aesthetics. Moreover, primary teeth serve as guides for the proper eruption of permanent teeth. Therefore, maintaining the cleanliness and health of children's teeth from an early age is crucial to prevent the formation of stains and discoloration, which can have long-term effects on both function and appearance.Preventive efforts through education on proper oral hygiene habits, avoiding substances that contribute to staining, and regular dental visits are essential strategies in preserving children's dental health. Early intervention and awareness can significantly reduce the risk of staining and ensure that children's teeth continue to support their overall well-being throughout the stages of development